A family of double-beauty tetraquarks: Axial-vector state *The work of K. A, B. B., and H. S was Supported in part by the TUBITAK (119F050). (January 2021) - Agaev, S. S.; Azizi, K.; Barsbay, B.; Sundu, H.
Abstract: The spectroscopic parameters and decay channels of the axial-vector tetraquark (in what follows, ) are explored using the quantum chromodynamics (QCD) sum rule method. The mass and coupling of this state are calculated using two-point sum rules by taking into account various vacuum condensates, up to 10 dimensions. Our prediction for the mass of this state confirms that it is stable with respect to strong and electromagnetic decays and can dissociate to conventional mesons only via weak transformations. We investigate the dominant semileptonic and nonleptonic decays of . In these processes, is a scalar tetraquark built of a color-triplet diquark and an antidiquark, whereas M is one of the vector mesons, , , and . To calculate the partial widths of these decays, we use the QCD three-point sum rule approach and evaluate the weak transition form factors ( ), which govern these processes. The full width and the mean lifetime of the tetraquark are computed using the aforementioned weak decays. The obtained information about the parameters of and is useful for experimental investigations of these double-heavy exotic mesons.